Optimal Selection of Water Resource Allocation Schemes Considering the Impact of Water Resource Management - XIAO Yixuan; ZHENG Yanhui; HE Yanhu; CHEN Xiaohong; GU Xihui; TU Jingjing (Renmin Zhujiang)
Considering the impact of water resources management, with Dongguan City as an example, a comprehensive evaluation system consisting of water management, safety, economy, and environment index was constructed. A gray correlation coefficient was also introduced to establish a coupling model based on gray correlation-fuzzy comprehensive evaluation, to achieve the optimal selection of the water source allocation scheme. It was found that the water management index would affect the optimal selection result of the scheme. When the impact of water source management is not considered, the water economic index plays a leading role. The optimal scheme is 365 million m³/year of river-reservoir interconnection project (RRIP) and 95 million m³/year Pearl River Delta Water Resources Allocation project (PRDWRAP), while the alternative is 292 million m³/year of RRIP and 168 million m³/year of PRDWRAP. When the impact of water resources management is considered, the optimal scheme is 365 million m³/year of RRIP and 95 million m³/year of PRDWRAP, while the alternative is 37 million m³/year of RRIP, 330 million m³/year of PRDWRAP and 93 million m³/year of built water works. The index system and optimal model constructed in this study not only consider the current water supply cost, water supply guarantee rate and waste sewage discharge, but also the management difficulty in the future and the unknown following management cost. A more scientific and comprehensive decision-making basis for decision makers is thus provided.